Reviewon Malaysia’s GreenRE in comparison with Singapore’s GreenMark and UK’s BREEAM / Halmi Zainol ... [et al.] - Halmi, Zainol; Fadhilah, Che Aziz; Suharto, Teriman; Haryati, Mohd Isa; Muhamad Asri, Abdullah Kamar (2015)
The movement of green building was started after the Agenda21. International Council for Research and Innovation in Building and Construction highlighted the main challenges that sustainable development presents to the construction industry. The Agenda had an important role in the creation of green assessment tools in building industry. An international project coordinated from Canada namely GB Tool (Green Building Tool) was the first attempt to develop green rating tool. The awareness has emerged the implementation of various rating tools such as LEED, CASBEE, BREEAM and GreenMark developed by the United States of America, Japan, United Kingdom and Singapore respectively. Many rating systems can be developed in different regions that lookquite different, but share a common methodology and set of terms. In Malaysia, a new set of rating tool was developed by the Real Estate and Housing Developers Association (REHDA) known as GreenRE. This paper reviews the GreenRE and compare it with GreenMark and BREEAM. Since the latter were more established, this paper will study strengths, weaknesses, gaps and issue within the GreenRE. With the outcome of this study, it may help both the authority and industry-players to prepare a comprehensive assessment tool that suit to local practice.